Effect of Method and Type Additive Fertilization with Date Palm Wastes on Growth of Cucumber Plants under Open Field Conditions - M. M. Muslat (Journal of Global Pharma Technology, 2018)
This experiment was carried out in spring of 2017 in a field of the Horticulture department and Garden Engineering / College of Agriculture / Baghdad University (Abu-Ghraib) , alternative site for Anbar University, to study the effect of method and type of organic fertilization with Date palm waste (decomposed Date palm leaves and decomposed grinder Date palm seeds ) Add To the soil by weight : weight ratio and spraying the extract of decomposed grindery Date palm seeds on cucumber growth under field conditions, according to RCBD. Treatments included T0 was the control using recommended chemical fertilizer (260 kg urea / h + 340 kg super phosphate / h and 100 kg K / h using potassium sulphate) , T1 , T2 and T3 was organic fertilizer consisting of 2.5%, 5% and 7.5% decomposed Date palm leaves wastes respectively, T4, T5 and T6 fertilizing with 4%, 6% and 8% decomposed grindery Date palm seeds respectively, and T7, T8 and T9 addition of 2.5%, 5% and 7.5% decomposed Date palm leaves wastes respectively with foliar spray by extract of decomposed grindery Date palm seeds , T10 add organic fertilizer consisting of decomposed Date palm leaves 5% and 4% decomposed Date palm seeds . Half of the fertilizer recommendation was added to all organic fertilization treatments. The data were analyzed by Gen Stat program and the results were tested according to LSD test at a 0.05 probability level. The results showed that organic fertilization with decomposed Date palm leaves increased the vegetative growth. T9 exceeded most of the studied traits, It given 100% germination ratio, rate of leaf area was 4305 cm2, phosphorus ratio in leaves was 0.3833, potassium in leaves was 1.2000%. T5, T4 and T6 were exceeded significantly about the other treatments in speed of germination were 7.24, 6.75 and 6.60 plant per day respectively. T8 given highest rate of plant height was 175.1 cm. T7 given highest chlorophyll content in plant leaves was 62.10 Spad. T3 given highest dry mater of vegetative part was 11.17%.Keywords: Organic fertilization, Foliar application, Date palm wastes, Plant extract Cucumber.